(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Successful rehabilitation of a dentition having a poor prognosis with implant-supported fixed prosthesis is a multi-stage process involving an edentulous period before prosthetic rehabilitation of the patient. The period of transformation from natural teeth to fixed implant prosthesis is sometimes not accepted by the patients. This concept has been in clinical use since 1998. This treatment is cost-effective and time-saving in order to rehabilitate patients with an interim prosthesis in which 4 implants were placed two placed vertically in the anterior region and two placed up to an angle of 45 degrees in the posterior region. Purpose: To evaluate Knowledge, Attitude and Practice among Dental practitioners about the “All on four” Concept of Dental implants practicing in Pimpri Chinchwad, Pune, Maharashtra, India. Methods: This quantitative-type descriptive survey was conducted between February to April 2022 in Pimpri Chinchwad, Pune, Maharashtra, India. A self-designed, pre-tested and validated questionnaire assessing the Knowledge, Attitude and Practice among Dental practitioners about the "All on four" Concept of Dental implants. Data were collected and entered into a spreadsheet (Excel 2010: Microsoft office) and analyzed using SPSS software (version 19-SPSS Inc. Chicago, IL, USA). Results: All 205 participants responded. When asked if dental practitioners considered the "All on four" concept a viable option 74.1% of practitioners (152) agreed while about 25.9% of practitioners (53) did not agree on the same Conclusion: Despite the presence of knowledge and attitude among dental practitioners the presence of practice among practitioners seems to be insufficient towards the "All on Four Implant" Concept.